The Political Roles of The Royal Thai Navy between 1932 - 2014 - Palanan, Fhaprapai (The Journal of Development Administration Research, 2020)
This article aims to study 1) the political culture of the navy in the period 1932-2014 2) the political role of the navy in the period 1932 -2014 and 3) the culture and political roles of the navy that affected the development of Thai democracy in the period 1932-2014 This research uses qualitative research. With documentary research, and collecting data through document research and in-depth interviews, key informants were thai navy, use purposive sampling. The research found that 1) The political role of some sailors who participated in the change of government in 1932 is regarded as a person with confidence in the democratic regime. And the political role of the sailors in during the Manhattan uprising. By disagree with the junta’s government that does not operate the government for the benefit of the people. And after the Manhattan Rebellion ended. The sailors were reduced to political roles. Until the present day, the political role of the navy has remained in the same state or government. Authorities who want the navy to support only. 2) The political culture of the navy since, although the navy has participated in the change of rule. In 1932 Including becoming involved in political movements such as the Rebellion, the Royal Palace and the Manhattan Rebellion, and ultimately the navy has been reduced to a greater political role. Such characteristics demonstrated the naval culture of the navy. Can be said that the navy does not have a complete democratic political culture. 3)The political role political and the culture of the navy during the period 1932-2014 affected the development of Thai democracy as follows: (1) In the period of the change of government in 1932 (2) during the Manhattan Rebellion in 1950. (3) in the aftermath of the Manhattan Rebellion, and (4) in the present time.